The Moderating Role of Size in the Influence of Financial and Governance Aspects on Tax Avoidance - Deselva Sesilia; Ifah Rofiqoh (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Study This aiming for test hypothesis that profitability, capital intensity, and proportion commissioner independent is predictor significant to avoidance taxes, as well as that size company to moderate connection between third variable the with avoidance Tax. Urgency study This based on the increasing practice avoidance taxes that can be lower state revenue and inhibit effectiveness policy taxation. Research This use approach quantitative with secondary data obtained​ from report annual company public listed on the Indonesia Stock Exchange (IDX) during period 2019–2023. Purposive sampling technique was used for obtained 193 companies that met the requirements criteria certain. Although in accordance with objective research, engineering This own potential bias that can limit generalization Results. Analysis done with panel data regression using Random Effect Model (REM) approach. Research results show that profitability influential positive and significant to avoidance tax, indicating that more companies​ profitable own more lots of opportunities and incentives for do planning tax aggressive. Capital intensity and proportion commissioner independent no influential significant, which shows that second factor the no always related directly with behaviour avoidance tax. While that, size company proven to moderate connection between profitability and avoidance tax, but no to moderate relationship between two variables others. Findings this give contribution important for regulators, investors and academics in understand determinant avoidance tax as well as confirm the need for governance more companies​ effective for press practice the.